Chlorella vulgaris improves the regenerative capacity of young and senescent myoblasts and promotes muscle regeneration - Zainul Azlan, Nurhazirah; Mohd Yusof, Yasmin Anum; Alias, Ekram; Makpol, Suzana (Hindawi, 2019)
Sarcopenia is characterized by the loss of muscle mass, strength, and function with ageing. With increasing life expectancy, greater attention has been given to counteracting the effects of sarcopenia on the growing elderly population. Chlorella vulgaris, a microscopic, unicellular, green alga with the potential for various pharmaceutical uses, has been widely studied in this context. This study is aimed at determining the effects of C. vulgaris on promoting muscle regeneration by evaluating myoblast regenerative capacity in vitro. Human skeletal myoblast cells were cultured and underwent serial passaging into young and senescent phases and were then treated with C. vulgaris, followed by the induction of differentiation. The ability of C. vulgaris to promote myoblast differentiation was analysed through cellular morphology, real-time monitoring, cell proliferation, senescence-associated β-galactosidase (SA-β-gal) expression, myogenic differentiation, myogenin expression, and cell cycle profiling. The results obtained showed that senescent myoblasts exhibited an enlarged and flattened morphology, with increased SA-β-gal expression, reduced myogenic differentiation, decreased expression of myogenin, and an increased percentage of cells in the G0/G1 phase. Treatment with C. vulgaris resulted in decreased SA-β-gal expression and promotion of myogenic differentiation, as observed via an increased fusion index, maturation index, myotube size, and surface area and an increased percentage of cells that stained positive for myogenin. In conclusion, C. vulgaris improves the regenerative capacity of young and senescent myoblasts and promotes myoblast differentiation, indicating its potential to promote muscle regeneration.